2008
DOI: 10.1515/advgeom.2009.006
|View full text |Cite
|
Sign up to set email alerts
|

Almost g.o. spaces in dimensions 6 and 7

Abstract: Some pseudo-Riemannian modifications of 6-dimensional and 7-dimensional Riemannian g.o. spaces are presented as pseudo-Riemannian homogeneous spaces with noncompact isotropy groups. These examples have the property that all geodesics are homogeneous up to a set of measure zero. Based on these examples, conjectures on geodesic graphs are formulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Recall the conjecture in the Introduction. The geodesic lemma allows us to rephrase its statement: Conjecture 1 [8]. If an homogeneous space G/H is an almost g.o.…”
Section: An Almost Go Space Whose Null Homogeneous Geodesics Requirmentioning
confidence: 99%
See 1 more Smart Citation
“…Recall the conjecture in the Introduction. The geodesic lemma allows us to rephrase its statement: Conjecture 1 [8]. If an homogeneous space G/H is an almost g.o.…”
Section: An Almost Go Space Whose Null Homogeneous Geodesics Requirmentioning
confidence: 99%
“…To conclude this work we consider the following conjecture posed by Dušek in [8]: Conjecture 1: If an homogeneous pseudo-Riemannian space is a geodesic orbit space or an almost geodesic orbit space, then the parameter of the oneparameter group whose orbit is a null geodesic is an affine parameter for the geodesic.…”
Section: Introductionmentioning
confidence: 99%
“…spaces and even for all known almost g.o. spaces [5,8], we have observed that each homogeneous geodesic is expressed through the affine parameter.…”
Section: Conventionmentioning
confidence: 99%
“…In these papers, each geodesic vector X is characterized by the formula (1.2). See also [4,5,7,8]. A rigorous mathematical proof of this characterization is given in [7]:…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is conjectured that a pseudo-Riemannian g.o. space with non-compact isotropy group should be naturally reductive [9].…”
Section: Introductionmentioning
confidence: 99%